Structural Syndemics and Antiretroviral Medication Adherence Among Black Sexual Minority Men Living With HIV. (15th December 2021) - Holloway, Ian W.; Beltran, Raiza; Shah, Saanchi V.; Cordero, Luisita; Garth, Gerald; Smith, Terry; Wilson, Bianca D. M.; Ochoa, Ayako M.
Abstract : Background: Although HIV antiretroviral treatment (ART) access and uptake have increased among racial/ethnic minority individuals, lower rates of ART adherence and viral suppression persist, especially among Black men who have sex with men (BMSM) compared with their White counterparts. Setting: Black men who have sex with men living with HIV (BMSM+) residing in Los Angeles County (N = 124) were recruited in-person (eg, clinic) and online (eg, social networking apps). Methods: Participants completed a cross-sectional survey measuring demographic characteristics, structural syndemics (poverty, criminal justice involvement, and housing instability), and psychosocial syndemics (mental health and substance use). A text message survey assessed missed doses of ART over the past week. Zero-inflated Poisson regression models were used to evaluate variables associated with the number of missed doses of ART. Results: On average, participants missed 1.30 doses of ART (SD = 2.09) and reported structural syndemics: poverty (56.1%), criminal justice involvement (36.6%), housing instability (26.3%), and psychosocial syndemics: childhood sexual abuse (51.8%), intimate partner violence (16.9%), depression (39%), and problem alcohol use (15.5%). After controlling for employment, age, education, and psychosocial syndemics, participants with a one-point increase in structural syndemic indicators were found to be 1.63 times more likely to have missed a dose of ART. Conclusions: Structural syndemic were associated with ART nonadherence among BMSM+ after adjusting for demographic and psychosocial factors. HIV treatment interventions that incorporate financial incentives, legal support, and housing may help improve ART adherence among BMSM+. Findings suggest that key priorities to ending the HIV epidemic must include structural interventions that alleviate poverty, eliminate disproportionate policing and criminalization, and end homelessness.